Creating Public Awareness of Thalassemia as A Marketing Communication Strategy at Genetic Clinic Genneka - Kumoro, Wahyu; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2013)
Indonesia, with the population of almost 250 millions people, have high number of genetic disorders which should be treated and managed. One of genetic disorders in Indonesia with high number of registered patients is Thalassemia, a red blood cell disorders that cause severe anemia and required regular blood transfusion. Patients that have severe thalassemia disease could result in death before birth or at young age if not treated intensively. Genetic Clinic Genneka is a genetic clinic that is located at the Eijkman Institute for Molecular Biology, a research institute under the Indonesian Ministry of Research and Technology, which provides various services related to genetic diseases, especially thalassemia. The issue of this research is the low number of patients that come by their own initiative for this service compared to the potential patients. Based on the business issues exploration, which included internal, external, and SWOT analysis, the root problem found in this research is low awareness of the general public towards genetic diseases especially thalassemia. The SWOT analysis that described the strengths and weaknesses of the internal company, as well as opportunities and threats of the external environment, are further analyze to find out the company position and develop strategies through the use of SWOT Matrix and TOWS Matrix. The result was promotion strategy creation to increase public awareness of thalassemia disease. The business solution selected is promotion strategy through digital media and direct promotion. Â Keywords: Thalassemia, Promotion Strategy, Public Awareness